Discharge Practices in the University Clinical Setting - McNamara, Kevin M.; Hindenlang, Jane; Cascella, Paul W. (Contemporary Issues in Communication Science and Disorders, 2004)
This study investigated the degree to which clinic directors rated the influence of American Speech-Language-Hearing Association (ASHA) discharge criteria and organizational factors on client discharge in the university setting. Results found that university clinic directors regarded ASHA's client-centered criteria to more strongly influence client discharge practices than did organizational factors. In fact, organizational factors (e.e., fee structure, resources, scheduling, disorder characteristics) were revealed to have little to no influence on discharge practices. Results have implications for the pre-professional education of student clinicians in the university clinic and how student clinicians are oriented to discharge practices across a variety of clinical settings.
Keywords: dept.cmd

Pediatricians' opinions about otitis media and speech-language-hearing development - Sonnenschein, Esther; Cascella, Paul W (Journal of Communication Disorders, 2004)
Twenty-five pediatricians responded to a confidential survey about their opinions on the relationship between otitis media and children's speech-language-hearing status. Results found that pediatricians did not necessarily agree that otitis media has an impact on speech-language-hearing development. Pediatricians reported that an early otitis media onset (birth to age 2) affects speech-language development, but they also reported that parents and daycare environments could mitigate any otitis media effect. Pediatricians reported a possible otitis media impact on hearing status, but they did not necessarily agree that an otitis media history required referral for audiological testing. Clinical implications are discussed for collaboration among pediatricians, speech-language pathologists, and audiologists. Learning outcomes: (1) The reader will become familiar with pediatricians' opinions about the impact of otitis media on speech-language development. (2) The reader will become familiar with strategies to support interdisciplinary collaboration between pediatricians, speech-language pathologists, and audiologists. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: *Attitude to Health; *Hearing Disorders/ep [Epidemiology]; *Language Disorders/ep [Epidemiology]; *Otitis Media/ep [Epidemiology]; *Pediatrics; *Speech Disorders/ep [Epidemiology]; Child; Humans; Medical practices; Otitis media; Pediatricians; Speech-language development; dept.cmd; health survey; hearing; human; language development; medical practice; otitis media; pediatrician; questionnaire; review; speech development; thinking

Receptive communication abilities among adults with significant intellectual disability - Cascella, Paul W (Journal of Intellectual & Developmental Disability, 2004)
This study measured the receptive communication skills of 14 adults with significant intellectual disability living in community group homes in Connecticut. Group home staff members rated the 14 participants using it 14-item rating scale sensitive to the adult living situation. These individuals appeared to have relatively stronger skills for comprehension of single-step in-context directions and the ability to recognise that particular tangible objects represented certain daily routines. These individuals were relatively, weak in identifying,familiar people in photographs and common objects in magazines. Among these participants, persons with profound intellectual disability mere rated to hate lower receptive communication skills than persons with severe intellectual disability. Clinical implications are discussed for human service providers and education professionals.
Keywords: Down syndrome; adult; anxiety disorder; article; clinical article; depression; dept.cmd; developmental disorder; disability; disease severity; female; hearing loss; human; interpersonal communication; male; mental disease; psychosis; scoring system; seizure

Knowledge of autism spectrum disorders among connecticut school speech-language pathologists. - Cascella, Paul W; Colella, Catherine S (Focus on Autism and Other Developmental Disabilities, 2004)
This study utilized a rating scale and random sampling of Connecticut school speech—language pathologists about their preprofessional education and current knoWledge of autism spectrum disorders (ASD). The participants had a minimal amount of preprofessional academic or clinical preparation in ASD, and no differences Were found in hoW speech—language pathologists Were trained over the past 30 years. School speech—language pathologists reported relatively stronger knoWledge of the general behavioral and communication characteristics associated With ASD and less knoWledge of educational assessment and intervention formats. Given the prevalence of schoolchildren With ASD, speech—language pathology graduate programs need to enhance their preprofessional curricula to provide school-based speech—language pathologists With specific training to meet the communication needs presented by children With ASD. © 2004, Sage Publications. All rights reserved.
Keywords: dept.cmd

Adaptive behavior in autism and pervasive developmental disorder-not otherwise specified: Microanalysis of scores on the vineland adaptive behavior scales - Paul, R.; Miles, S.; Cicchetti, D.; Sparrow, S.; Klin, A.; Volkmar, F.; Coflin, M.; Booker, S. (Journal of Autism and Developmental Disorders, 2004)
The purpose of this study is to provide a microanalysis of differences in adaptive functioning seen between well-matched groups of school-aged children with autism and those diagnosed as having Pervasive Developmental Disorder-Not Otherwise Specified, all of whom functioned in the mild to moderate range of intellectual impairment. Findings indicate that the major area of difference between children with autism and those with Pervasive Developmental Disorder-Not Otherwise Specified, was expressive communication; specifically, the use of elaborations in syntax and morphology and in pragmatic use of language to convey and to seek information in discourse. Linear discriminant function analysis revealed that scores on just three of these expressive communication item sets correctly identified subjects in the two diagnostic categories with 80% overall accuracy. Implications of these findings for both diagnosis and intervention with children with Autism Spectrum Disorders will be discussed.
Keywords: Activities of Daily Living; Adaptation, Psychological; Adaptive behavior; Autism; Autistic Disorder; Child; Child Development Disorders, Pervasive; Child, Preschool; Communication; Discriminant Analysis; Expressive language; Female; Humans; Personality Tests; Pervasive Developmental Disorders; Social Behavior; Socialization; adaptive behavior; article; autism; brain function; child; clinical article; comparative study; controlled study; dept.cmd; developmental disorder; diagnostic accuracy; diagnostic approach route; female; functional anatomy; human; intellectual impairment; interpersonal communication; language; linear system; male; microanalysis; peer-reviewed; priority journal; rating scale; scoring system; socialization; treatment indication